The SeroNet Clinical and Translational Serology Task Force (CTTF) SARS-CoV-2 mucosal immunity methodological considerations and best practices workshop - Heidi Hempel; Nicholas Mantis; Christopher D. Heaney; Ligia A. Pinto (Taylor & Francis Group, 2023)
SARS-CoV-2 persists in certain populations, even with vaccination and boosters. Emerging evidence suggests that reductions in virus transmission and infection will likely require involvement of the mucosal immune system, especially secretory antibodies in the upper respiratory tract. The Clinical and Translational Serology Task Force (CTTF) within The National Cancer Institute (NCI)'s Serological Sciences Network for COVID-19 (SeroNet) hosted a workshop to review the status of development and standardization of mucosal sample collection methods and assays, identify challenges, and develop action plans to bridge gaps. Speakers presented data underscoring a role for secretory IgA in protection, mucosal markers as correlates of protection, methods for tracking and assessing mucosal antibodies, and lessons learned from other infectious agents. Perspectives from regulators and industry were put forward to guide mucosal vaccine development. Methodological considerations for optimizing collection protocols and assays and harmonizing data were highlighted. Rigorous studies, standardized protocols, controls, standards, and assay validation were identified as necessary to gain momentum in expanding SARS-CoV-2 vaccines to the mucosa.